(3eLehY aj GdcjejGAs - (3GadGWhf GdMcjes
(3ChdgG (B:s
(3bGd CadGWhf dJdejPg jG Hfi EPG CQOJ Md GdbdYi YGLdkG COHg HWGLf hGQLeg HcdS bTQ GdHjV eSMhbkG hGfJ JMQcg s
(3BNQgG (B:s
(3Ke HYO GdCKfG YTQ eQI JMW GdeYehd ai WGLf eOghf Ydi fGQ djfg EfTGA Gddg JYGdi s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdQGHYs
(3HBNQgG ahGFO hfbhd eNJdaI ai ehVhYGJ cjejGFjI eNJdaI hYOI hUaGJ cjejGFjIs
(3HgG fXGe GdJYbjHIs
(3eUOQ GbJfGA GdCUd (B:s
(3LGeYI jhJG s
Keywords: (3GdcjejGA h GdWHjYjGJs